ÖZNE--NESNE İKİLİĞİNİN ÖTESİNDE YÛNUS EMRE'DE TEVHÎD MERKEZLİ ESTETİK TECRÜBE. - ÇETİN, OĞUZ (Turkish Culture & Haci Bektas Veli Research Quarterly, 2026)
This study addresses the ontological and epistemological fragmentation in modern aesthetic thought, which is shaped by the subject-object dichotomy inherited from the Enlightenment, as a fundamental problem. The aim of the research is to reinterpret this issue by using the tawhīd-centered Sufi perspective of Yūnus Emre as an analytical framework. In this context, Yūnus Emre's ontology--which conceives the human being as a holistic entity of intellect, soul (jān), ego (nafs), body, and heart (gönül)--demonstrates that the aesthetic subject is not a static structure but a dynamic process shaped by the struggle between the 'ego-sultan' and the 'soul- sultan' in the 'realm of the heart'. The methodology of the study is based on conceptual analysis and textual close reading. Accordingly, it examines how aesthetic perception is transformed through a 'transmutation of taste' (dhawq tabdīlī) during the spiritual journey (sayr wa sulūk) and how purified senses like the 'eye of the soul' (jān gözü) elevate aesthetic experience into an epistemic apprehension (idrāk). Furthermore, the layered structure of the aesthetic object-- as form (sūrat), meaning (ma'nā), a veil (parda), and a locus of manifestation (mazhar)--is analyzed to reveal that aesthetic experience is a holistic encounter beyond mere subjective pleasure. This study is significant for demonstrating, through the works of Yūnus Emre, that aesthetics cannot be considered separately from ethical and ontological transformation.